Mercer’s Theorem, Feature Maps, and Smoothing - Minh, Ha Quang; Niyogi, Partha; Yao, Yuan (Learning Theory, 2006)
We study Mercer’s theorem and feature maps for several positive definite kernels that are widely used in practice. The smoothing properties of these kernels will also be explored.